2022
DOI: 10.1002/pdi.2378
|View full text |Cite
|
Sign up to set email alerts
|

Eye problems in people with diabetes: more than just diabetic retinopathy

Abstract: While diabetic retinopathy and maculopathy are leading causes of premature visual loss in people with diabetes, other retinal and non-retinal pathology should be considered in the differential diagnosis. These include issues with both eye movement and vision, and can be split into: those which are extraocular, including orbital cellulitis and cranial nerve palsies; those in the anterior segment, including dry eyes, visual disturbances, superficial eye infections, anterior uveitis, cataracts and neovascularisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
3
0
1
Order By: Relevance
“…Clinically, hypoxia-associated progression of retinopathy is observed in a diabetic patient. Chronic diffuse retinal ischemia is also known to cause visual field impairment in patients with diabetic retinopathy [46]. Our experimental research revealed similar kinds of visual defects in diabetic mice.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Clinically, hypoxia-associated progression of retinopathy is observed in a diabetic patient. Chronic diffuse retinal ischemia is also known to cause visual field impairment in patients with diabetic retinopathy [46]. Our experimental research revealed similar kinds of visual defects in diabetic mice.…”
Section: Discussionsupporting
confidence: 70%
“…resulted in the development of DR. It is mainly due to the enlargement of retinal blood vessels, extravasation of blood vessels, extensive vacuolations, and disarrangement of retinal cell layers in the vitreous regions [45,46]. In addition, DR animals had visual acuity changes i.e., decrease the in SFT value in the OMR test and increase in the number of errors in the PM test.…”
Section: Discussionmentioning
confidence: 99%
“…in diabetic mice demonstrated a significant ( p < 0.05) indication of DR via the changes in blood–retina barrier functions. The manifestations of DR were microaneurysm, intraretinal hemorrhage, exudate, macular edema, macular ischemia, and neovascularization [ 33 , 34 ]. Furthermore, STZ altered visual acuity by decreasing the SFT value in the OMR test, increasing the time of RVCP, and decreasing the TSTQ values in the VCFT test.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of diabetes mellitus and its associated complications are major concerns in diabetes care epidemiology in India 58 . Among various co-morbidities, eye problems are common among diabetic patients 59 61 . Empirical evidences suggest that, Asian Indian people are characterized by high levels of intra-abdominal fat and insulin resistance which prompts them to type-2 diabetes 62 .…”
Section: Discussionmentioning
confidence: 99%